Comparison of muscle activation during elliptical trainer, treadmill and bike exercise - Sözen, H. (Biology of Sport, 2010)
The purpose of this study is to compare muscle activation during elliptical trainer (ET), treadmill (TM) and bike (B) exercise. Twenty three voluntary and healthy male athletes (age, 20.65±1.65 years; weight, 74.21±7.21 kg; height, 180.69±5.31 cm; Body Mass Index, 22.4±1.5) participated in our study. Study protocol was decided for three days. Measures were taken by using elliptical trainer on the first day, treadmill on the second day and bicycle device on the third. Exercise devices were run with 65% metabolic pulse for six minutes and at the end of the sixth minute, surface electrodes were placed on Biceps Brachii, Triceps Brachii, Pectoralis Major and Trapezius of upper extremity muscle and on Gastrocnemius, Vastus Lateralis, Rectus Femoris and Gluteus Maximus of lower extremity muscles and Electromyography (EMG) activities were measured. According to the finding of the study, it has been found out that all of the measured upper extremity muscle were more activated by elliptical trainer compared to treadmill and bike exercise (p<0.05). Also, it has been found out that Gastrocnemius and Gluteus Maximus of lower extremity muscle were more activated by treadmill compared to other exercise devices (p<0.05). Rectus Femoris muscle was more activated by elliptical trainer compared to bike exercise (p<0.05). EMG results of Vastus Lateralis did not show any statically differences (p>0.05). In conclusion, due to the advantage of more upper extremity muscle activation, it has been thought that elliptical trainer is a device to be able to be used in rehabilitation and exercise science.